2018
DOI: 10.1242/dev.158865
|View full text |Cite|
|
Sign up to set email alerts
|

Fat body glycogen serves as a metabolic safeguard for the maintenance of sugar levels in Drosophila

Abstract: Adapting to changes in food availability is a central challenge for survival. Glucose is an important resource for energy production, and therefore many organisms synthesize and retain sugar storage molecules. In insects, glucose is stored in two different forms: the disaccharide trehalose and the branched polymer glycogen. Glycogen is synthesized and stored in several tissues, including in muscle and the fat body. Despite the major role of the fat body as a center for energy metabolism, the importance of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(120 citation statements)
references
References 55 publications
7
113
0
Order By: Relevance
“…We previously reported that periodic acid-Schiff (PAS) staining reliably visualizes stored glycogen and also detects mobilization upon brief starvation in the fat body (Yamada et al, 2018). Consistent with our previous research (Yamada et al, 2018), GlyS mutants showed strong reductions in the PAS signal in tissues such as the CNS, the fat body and body wall muscles. This reduction was fully rescued by the ubiquitous expression of C-terminal Flagtagged GlyS by Tub-Gal4 (Fig.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…We previously reported that periodic acid-Schiff (PAS) staining reliably visualizes stored glycogen and also detects mobilization upon brief starvation in the fat body (Yamada et al, 2018). Consistent with our previous research (Yamada et al, 2018), GlyS mutants showed strong reductions in the PAS signal in tissues such as the CNS, the fat body and body wall muscles. This reduction was fully rescued by the ubiquitous expression of C-terminal Flagtagged GlyS by Tub-Gal4 (Fig.…”
Section: Introductionsupporting
confidence: 80%
“…Liver glycogen plays an important role in the glucose cycle to maintain circulating sugar levels, whereas muscle glycogen is directly utilized through glycolysis to maintain muscle activities (Roach et al, 2012;Petersen et al, 2017). In Drosophila larvae, we have shown previously that the tissue-specific regulation of glycogen metabolism in the fat body, an organ equivalent to the mammalian liver, plays a crucial role in the maintenance of circulating sugars under fasting conditions (Yamada et al, 2018). In adults, glycogen is stored in flight muscles and consumed during flight (Wigglesworth, 1949).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, up-regulation of TO in the hindgut at PI 12-27 suggests that L. passim -infected honey bees were under starvation. Trehalose levels in the hemolymph are reduced in the fruit fly under starvation (Yamada et al 2018) and this is consistent with the increase of Tret1 mRNA in the hindgut of L. passim -infected honey bees at PI 7-20. The decrease in hemolymph trehalose levels is caused by its reduced release from fat bodies and increased uptake by various tissues.…”
Section: Discussionsupporting
confidence: 75%
“…Figure 4D for dilp3 mutant). This suggests that a lack of DILP3 may result in conversion of glycogen stores into trehalose instead of glucose (Yamada et al, 2018). This possible conversion was inhibited by an increased intake of protein.…”
Section: Discussionmentioning
confidence: 99%